Retrospective Evaluation of Root End Resection without Retrograde Filling - GÖÇMEN, GÖKHAN; ÖZKAN, YAŞAR (AVES PRESS LTD, 2018)
Objective: The aim of the present study was to investigate the outcomes of cases completed without retrograde filling following root end resection made for periapical pathology. Methods: This was a retrospective cohort study. The primary predictor variables included gender, age (>45 vs <45 years), and localization (maxilla, mandible, anterior, and posterior). The primary outcome variable was radiological assessment (success vs failure). Data were analyzed by chi-square test and descriptive statistics (p<0.05). Results: A total of 56 (21 males and 35 females) patients were included in the study. Overall, 37 (66%) patients were successful, whereas 19 (34%) failed. Gender, age, and localization did not significantly affect the outcomes. There were significantly less successful outcomes in the posterior dentition (p<0.05). Conclusion: It cannot be reported that retrograde filling after root end resection is unnecessary; however, successful outcomes might be obtained without retrograde filling.
Keywords: Root end resection; retrograde filling; periradicular inflammation; MINERAL TRIOXIDE AGGREGATE; FOLLOW-UP; ENDODONTIC INFECTION; PERIAPICAL SURGERY; REGENERATION; APICECTOMY; AMALGAM; TRIAL; PART; MTA